A registry-based follow-up study, comparing the incidence of cardiovascular disease in native Danes and immigrants born in Turkey, Pakistan and the former Yugoslavia: do social inequalities play a role? - Andreasen Anne H; Diderichsen Finn; Nielsen Signe S; Larsen Finn B; Hempler Nana F; Jørgensen Torben (BMC, 2011)
Abstract Background This study compared the incidence of cardiovascular disease (CVD) and acute myocardial infarction (AMI) between native Danes and immigrants born in Turkey, Pakistan and the former Yugoslavia. Furthermore, we examined whether different indicators of socioeconomic status (SES), such as employment, income and housing conditions influenced potential differences. Methods In this registry-based follow-up study individuals were identified in a large database that included individuals from two major regions in Denmark, corresponding to about 60% of the Danish population. Incident cases of CVD and AMI included fatal and non-fatal events and were taken from registries. Using Cox regression models, we estimated incidence rates at 5-year follow-up. Results Immigrant men and women from Turkey and Pakistan had an increased incidence of CVD, compared with native Danish men. In the case of AMI, a similar pattern was observed; however, differences were more pronounced. Pakistanis and Turks with a shorter duration of residence had a lower incidence, compared with those of a longer residence. Generally, no notable differences were observed between former Yugoslavians and native Danes. In men, differences in CVD and AMI were reduced after adjustment for SES, in particular, among Turks regarding CVD. In women, effects were particularly reduced among Yugoslavians in the case of CVD and in Turks in the case of CVD and AMI after adjustment for SES. Conclusions In conclusion, country of birth-related differences in the incidence of CVD and AMI were observed. At least some of the differences that we uncovered were results of a socioeconomic effect. Duration of residence also played a certain role. Future studies should collect and test different indicators of SES in studies of CVD among immigrants.